Hubungan Tekanan Kerja dan Kepuasan Kerja dengan Komitmen Terhadap Organisasi: Satu Kajian di Ibu Pejabat Jabatan Kerja Raya Malaysia - Doraisamy, Gnana Sekaran (2007)
This analysis has been conducted to analyze levels, correlations and influence of work stress attributes (Workload and Resource Inadequacy) and job satisfaction attributes (Working conditions, Work itself, Supervision, Carrier Promotions, Co-workers and Pay) towards organizational commitment among the technical personnel in JKR Malaysia Headquarters in Kuala Lumpur.